Ідентифікація та оцінка кредитного ризику комерційних банків - Просович, О. П.; Процак, К. В.; Prosovych, O.; Protsak, K. (Видавництво Львівської політехніки, 2017)
У статті розкрито суть та види кредитних ризиків комерційних банків. Висвітлено основні чинники кредитного ризику за видами кредитних ризиків. Проаналізовано динаміку нормативів кредитних ризиків банківської системи України за останнє десятиліття. Проведено оцінку кредитних ризиків банківської системи України за новою методикою НБУ. Визначено основні чинники гальмування кредитної активності комерційних банків запропоновано заходи для покращення кредитної активності та якості кредитного портфелю банків.

The essence and types of credit risks of commercial banks are described in the article. The main factors of credit risk by types of credit risks are presented. Particular attention is paid to individual and portfolio credit risk. The types of active operations on which determine the credit risk are defined. The dynamics of credit risk norms of the Ukrainian banking system over the last ten years has been analysed. In the most acute phases of both financial crises that occurred during the analysed period, the values of credit risk norms were within the recommended limits. After analysing the actual values of the credit risk norms of the Ukrainian banking system from 2008, we conclude that by 2014 all the indicators did not exceed the limit values. The content of the new rules for assessing the size of credit risk and asset categorization is described. Using the new methodology of the National Bank of Ukraine the credit risk assessment of the Ukrainian banking system was carried out. Studies have shown that in 2017 the part of non-performing loans is more than half of loans of Ukrainian banks. The largest credit risk is assumed by state banks. The level of dollarization of loans and deposits of banks is increased as a result of the revaluation of balances against the background of a decline in the rate of the national currency. The main factors of inhibition of commercial banks credit activity are determined. The recommendations for state authorities and banks are presented in the end of the article. The measures were proposed to improve the credit activity and quality of the bank’s loan portfolio.
Identification and assessment of credit risk of commercial banks
Keywords: банківська система; кредитний ризик; нормативи кредитного ризику; непрацюючі кредити; bank system; credit risk; credit risk norms; non-performing loans; 330.4; 336.71